Multilocus phylogeny and taxonomic revision of the Hemidactylus robustus species group (Reptilia, Gekkonidae) with descriptions of three new species from Yemen and Ethiopia - Šmíd, Jiří; Moravec, Jiří; Kratochvíl, Lukáš; Nasher, Abdul K.; Mazuch, Tomáš; Gvoždík, Václav; Carranza, Salvador (Systematics and biodiversity, 2015)
The gecko genus Hemidactylus, with its 132 currently recognized species, ranks among the most species-rich reptile genera. Recent phylogenetic studies disclosed unexpectedly high genetic variability and complex biogeographic history within its arid clade distributed in the Mediterranean, Northeast Africa, Middle East and the Indian subcontinent. Particularly, the species from the Arabian Peninsula have been lately the subject of many taxonomic revisions that have resulted in the descriptions of 16 new taxa. Yet not all detected cryptic lineages have been treated taxonomically and thoroughly investigated morphologically. Based on phylogenetic analyses of two mtDNA (12S, cytb) and four nDNA (cmos, mc1r, rag1, rag2) gene fragments of a total length of 4015 bp in combination with analysis of morphological characters, we reinvestigate the systematics of the H. robustus species group consisting of the widespread H. robustus and three undescribed species, two of which occur in Southwest Yemen and one in central Ethiopia. By comparing two phylogenetic inference methods, concatenated gene trees and species-tree estimation, we reconstruct the phylogeny of the H. robustus species group. The coalescent-based species-tree estimation resulted in different tree topology than the concatenation approach, being probably a result of incomplete lineage sorting of ancestral polymorphism, suggesting that the H. robustus species group is in a stage of incipient speciation. The degree of differentiation of the characters examined within the H. robustus species group allowed us to provide a redescription of H. robustus and formally describe three new species of Hemidactylus - H. adensis sp. nov. and H. mandebensis sp. nov. from Yemen and H. awashensis sp. nov. from Ethiopia.